Antitumor activity of tripterine via cell-penetrating peptide-coated nanostructured lipid carriers in a prostate cancer model - Yuan L (Dove Medical Press, 2013)
Ling Yuan,1 Congyan Liu,2 Yan Chen,2 Zhenhai Zhang,2 Lei Zhou,1 Ding Qu2 1Department of Pharmaceutics, School of Pharmacy, Jiangsu University, Zhenjiang, Jiangsu, 2Key Laboratory of New Drug Delivery System of Chinese Materia Medica, Jiangsu Provincial Academy of Chinese Medicine, Nanjing, Jiangsu, People's Republic of China Background: The purpose of this study was to evaluate the antitumor effect of cell-penetrating peptide-coated tripterine-loaded nanostructured lipid carriers (CT-NLC) on prostate tumor cells in vitro and in vivo. Methods: CT-NLC were developed to improve the hydrophilicity of tripterine. The antiproliferative effects of CT-NLC, tripterine-loaded nanostructured lipid carriers (T-NLC), and free tripterine in a human prostatic carcinoma cell line (PC-3) and a mouse prostate carcinoma cell line (RM-1) were evaluated using an MTT assay. The advantage of CT-NLC over T-NLC and free tripterine with regard to antitumor activity in vivo was evaluated in a prostate tumor-bearing mouse model. The induced tumor necrosis factor-alpha and interleukin-6 cytokine content was investigated by enzyme-linked immunosorbent assay to determine the effect of CT-NLC, T-NLC, and free tripterine on immune responses. Histologic and TUNEL assays were carried out to investigate the mechanisms of tumor necrosis and apoptosis. Results: CT-NLC, T-NLC, and free tripterine showed high antiproliferative activity in a dose-dependent manner, with an IC50 of 0.60, 0.81, and 1.02 µg/mL in the PC-3 cell line and 0.41, 0.54, and 0.89 µg/mL in the RM-1 cell line after 36 hours. In vivo, the tumor inhibition rates for cyclophosphamide, high-dose (4 mg/kg) and low-dose (2 mg/kg) tripterine, high-dose (4 mg/kg) and low-dose (2 mg/kg) T-NLC, high-dose (4 mg/kg) and low-dose (2 mg/kg) CT-NLC were 76.51%, 37.07%, 29.53%, 63.56%, 48.25%, 72.68%, and 54.50%, respectively, showing a dose-dependent pattern. The induced tumor necrosis factor-alpha and interleukin-6 cytokine content after treatment with CT-NLC and T-NLC was significantly higher than that of high-dose tripterine. Moreover, CT-NLC showed the expected advantage of inducing necrosis and apoptosis in prostate tumor cells. Conclusion: CT-NLC noticeably enhanced antitumor activity in vitro and in vivo and showed dramatically improved cytotoxicity in normal cells in comparison with free tripterine. In summary, CT-NLC could be used as a promising drug delivery system for the treatment of prostate cancer. Keywords: cell-penetrating peptide, nanostructured lipid carriers, tripterine, prostate cancer, antitumor activity